What are we measuring with GABA magnetic resonance spectroscopy? - Stagg, C; Bachtiar, V; Johansen-Berg, H (2011)
A number of recent papers1-3 have demonstrated a relationship between in vivo concentration of GABA, as assessed using Magnetic Resonance Spectroscopy (MRS), and an individual's task performance, giving a unique insight into the relationship between physiology and behavior. However, interpretation of the functional significance of the MRS GABA measure is not straightforward. Here we discuss some of the outstanding questions as to how total concentration of GABA within a cortical region relates to phasic and tonic GABA activity within the cortical volume studied.